Rancang Bangun Prototipe PLTPh Sebagai Listrik Penerangan Kapasitas 9 Watt - Muhammad Ibrahim; Iman Dirja; Viktor Naubnome (Department of Mechanical Engineering, University of Udayana, 2020)
This study aims to realize the manufacturing of a prototype design of a pico-hydro power plant, which is expected to be a science of study and a reference for students at the University of Singaperbangsa Karawang in particular and Indonesian students in general, as well as monitoring the performance test of the prototype of pico-hydro power plant that is used as an electricity needs for lighting. The design and manufacture of this prototype require several supporting components: a). Pressure gauge; b). Pelton type turbines; c). Tacho Meter; d). Single-phase Ac generator; e). Avometer; f). Energy saving LED lamp. Pico-hydro power plant prototype testing is carried out by measuring the voltage generated by the generator, tested at no load and given a load using variations of 55%, 70%, 85%, 100% valve openings. Based on the results of the performance test, the pico-hydro power plant can work well. That matter can be seen from the largest flow valve opening which results in a high water flow rate, so that it can rotate the turbine quickly. The flow rate greatly affects the generator rotation. No-load test results, the largest voltage of 90 volts is obtained when using 100% valve opening, with the output producing an air flow of 0.0017 m3 / s, rotation (N1) 136 rpm, rotation (N2) 979 rpm. The results with the load, the largest voltage of 60 volts is obtained when using 100% valve openings, with the output producing rotation (N1) 133 rpm, rotation (N2) 957 rpm, and current 0.13 A when supplying the 4 LED lamps type of 3 watts with litting up brightly.